Pelatihan Toefl Preparation Course Bagi Mahasiswa Program Studi Pendidikan Matematika Fakultas Fkip Universitas Batanghari - Efa Silfia; Sri Dewi; Khidayatul Munawwaroh; Eka Melati; Lis Hafrida (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Mastery of foreign languages, especially English, is very important in efforts to improve the quality of human resources in the world of education. By imposing international quality standards, a campus has committed to enter a management domain that is no longer based on local quality standards and demands. Bilingual delivery of materials is a mandatory requirement for international standard schools. Of course, this is impossible if the teachers/teachers do not have English language competence. TOEFL equivalent English training is one of the efforts that can be done to improve the ability to master English for Mathematics students. Therefore, a TOEFL Preparation Course training program was conducted for students of the Mathematics Education study program FKIP Unbar to improve students' English skills. This program is carried out for 4 months. The training is divided into three basic skills, namely, Listening, Structure and Written Expression, and Reading Comprehension. Each session is held for 90 minutes with a balance of theory and practice in the form of working on practice questions. Meanwhile, to determine the initial and final abilities of the participants, a pre-test and post-test were carried out with TOEFL equivalent English test material. The results of this activity showed that students were satisfied and enthusiastic about participating in the training. In addition, there was an increase in students' English skills as indicated by an increase in post-test scores.